2019–2020 Florida Citrus Production Guide: Grove Planning and Establishment - Christopher Vincent; Tripti Vashisth; Mongi Zekri; Ute Albrecht (EDIS, 2019)
This 6-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. This chapter addresses the most important decisions that should be made before and immediately after planting and refers to other chapters with more detailed information. Generally, the most important factors before planting fall into site selection and grove planning and preparation. Planting and early tree care are also essential to long-term grove success. Coordinated planning of all aspects of grove establishment and careful planting establishment can set you up for success and reduced frustration in the future. Written by Christopher Vincent, Tripti Vashisth, Mongi Zekri, and Ute Albrecht, and published by the Horticultural Sciences Department, March 2019.